The great music caper [videorecording (DVD)] - Villamizar, Marco; Bow Wow (Musician); JoJo, 1990-; Marin, Cheech (Weinstein Co. ; Distributed by Vivendi Entertainment, 2010)
When sweet little Dizzy and smart-aleck Bop meet, the last thing they're expected to do is become friends. But when they decide to rescue their musical, magical land from an evil villain, the brave duo inspires harmony among other instruments far and wide.